Risk factors associated with growth failure in the follow-up of very low birth weight newborns - Rover,Milene M.S. (2016)
Abstract Objective: To determine risk factors during neonatal hospital stay and follow-up associated with failure to thrive in the first year of life of very low birth weight newborns. Methods: Study of preterm very low birth weight newborns followed from 2006 to 2013 in a public institutional hospital program. The study included newborns that attended at least one appointment in each of the three periods: Period I, up to 3 months of corrected age (CA); Period II, 4-6 months of CA; and Period III, 7-12 months of CA. The variables were analyzed by logistic regression with XLSTAT 2014 software (Microsoft®, WA, USA). Failure to thrive (Z-score below -2 SD) was classified as a dichotomous dependent variable (0 - failure/1 - success), while the other variables were classified as explanatory variables for the hospitalization periods and for each of the follow-up periods (I, II, and III). Results: Children born adequate for gestational age increased the chance of Z-score for weight at discharge > -2 SD (OR = 10.217; 95% CI: 1.117-93.436). Metabolic bone disease and retinopathy of prematurity in Period I, as well as hospital readmissions in Periods II and III during follow-up increased the chance of Z-score < -2 SD. Conclusion: Failure to thrive is influenced by intrauterine factors and, subsequently, by several morbidities, both in the birth and hospitalization period, as well as in the post-discharge period and thus, such variables should be prioritized in the follow-up.